(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article is dedicated to the studies of the state of gender approach implemented into the syseem of higher education in Canada, and is also aimed at knowłedge developmeni about internationał experience deal- ing wich gende echcation. The author covers the practice and peculiarities of wo nmain forms f gender krowledge spreading in universities and insitutes: women and gender studies.